Effects of dietary gamma-linolenic acid-rich borage oil combined with marine fish oils on tissue phospholipid fatty acid composition and production of prostaglandins E and F of the 1-, 2- and 3-series in a marine fish deficient in Delta 5 fatty acyl desaturase - Tocher, Douglas R; Bell, J Gordon; Farndale, Bruce M; Sargent, John R (Prostaglandins, Leukotrienes and Essential Fatty Acids, 1997)
The effects of γ-linolenic acid-rich borage oil (BO), in combination with different marine oils, namely an eicosapentaenoic acid (EPA) rich oil (MO) or a DHA-rich oil (TO), on tissue fatty acid composition and prostaglandin production were investigated in turbot, a species which lacks appreciable Δ5 fatty acyl desaturase activity. The juvenile turbot grew well on the experimental diets and there were no significant differences in final weights between dietary treatments. Irrespective of the marine oil component, both the BO-containing diets increased tissue phospholipid levels of 18:2n-6 and 18:3n-6, and their respective elongation products, 20:2n-6 and 20:3n-6, compared to fish fed a control diet containing a standard Northern hemisphere fish oil. Both the BO-containing diets increased the production of 1-series prostaglandins (PG), this being observed across all tissues investigated with PGF and especially PGE. The BO/MO diet also reduced 20:4n-6 in tissue phospholipids without affecting 20:5n-3, whereas the BO/TO combination decreased 20:5n-3 but increased 20:4n-6. The production of 2-series and 3-series PGs was also altered by the dietary treatments but the changes were less dependent upon the tissue levels of their respective precursor fatty acids, 20:4n-6 and 20:5n-3. The BO-containing diets had very significant effects on gross fatty acid compositions of the phospholipids including increased proportions of saturated fatty acids and n-6 polyunsaturated fatty acids (PUFA) and decreased proportions of monounsaturated fatty acids and n-3 PUFA. Overall, this study shows that eicosanoid production in turbot tissues can be influenced by dietary fatty acids, not only by changes in the absolute and relative levels of specific eicosanoid precursor PUFA in tissue phospholipids, but also by general effects on membrane composition, structure and function induced by gross fatty acid compositional changes.